Criteria and indicators of synergistic efficiency of food industry enterprise management - Kondratiev, D V; Osipov, A K; Gainutdinova, E A; Abasheva, O V; Ostaev, G Ya (IOP conference series. Earth and environmental science, 2022)
A synergistic approach to production management is becoming fundamental in ensuring the sustainable and efficient functioning and development of organizations. The aim of the study is to substantiate the methodological toolkit for assessing the synergistic management efficiency of the food industry enterprise. The paper briefly examines the positions of individual scientists, revealing the view of modern science on understanding synergy, the sources of its origin and approaches to the extraction of synergistic effect in the economy, business, and production. As a result of generalization of the research previously presented in science, the authors clarified and systematized the factors and conditions of synergy, which are divided into two groups - internal and external. On the basis of the system of synergy factors, the article substantiates a formalized system of criteria and indicators for assessing the synergetic efficiency of managing a food industry enterprise. The paper provides an example of calculating and evaluating the proposed criteria and indicators based on materials from one of the food industry enterprises, as well as reasoning and conclusions about the future actions of the management of this enterprise. The presented system of criteria and indicators makes it possible to judge the level of synergistic efficiency of management and the degree of influence of individual factors of synergy on the financial results of the enterprise. The technique can be used by the management of enterprises in the development and substantiation of promising (medium-term) management decisions and programs for the development of enterprises.